Design and preparation of beverage on golden berry (Physalis peruviana) enriched with kiwicha - Hernández Fernández, Eloísa (2019)
The development of products derived from native Andean functional foods is strategic for the biocommerce of agricultural products. The objective was to make a golden berry drink enriched with kiwicha. In a factorial design of 3 levels of kiwicha and 2 of golden berry, it was possible to select a drink based on sensory and viscosity attributes. The process: elaboration, pasteurization, packaging and storage at 6 ° C, was carried out in the Research Laboratory of “Special Bromatology and Nutritional Technology”. The sensory characteristics were determined by the quantitative descriptive method with a 5-point hedonic scale and a panel of trained evaluators. The physicochemical and microbiological characterization was performed according to official AOAC and ICMSF methods. The nutritional quality indicator amino acid profile was determined by high performance liquid chromatography. The most relevant results were: the attributes color (4,4 points), flavor (4,3 points); provitamin A (1050 μg%); vitamin C (6,5 mg%); lysine (74 mg%). In microbiological analyzes: viable mesophilic aerobes (<10 cfu/mL), total coliforms (<3 NMP7mL), molds and yeasts (<10 cfu/mL) and Escherichia coli (absent). The chemical-toxicological analysis did not detect cadmium or lead. The stability at 30 days of storage, there was no significant variation (95% confidence interval) in the sensory attributes with respect to the recent brewed beverage. It is concluded that the enriched drink is of high acceptability, stable, innocuous, meets microbiological specifications and can provide essential nutrients in a significant amount to the nutritional requirements of preschool children, adolescents and human adults.